2011
DOI: 10.1097/coh.0b013e328349b0a0
|View full text |Cite
|
Sign up to set email alerts
|

A look at HIV journey

Abstract: It is becoming evident that a better characterization of the early events of HIV transmission and the involvement of dendritic cell subtypes in this process would contribute to strengthen our efforts to improve the current therapeutic and prophylactic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…CXCR6 is also involved in the formation of the immunological synapse upon interaction with its ligand CXCL16, a membrane-bound chemokine expressed by DC [62,93]. This interaction my lead to efficient transmission of HIV within the virological synapse [94]. CXCL16 is also expressed by CD16 + monocytes [95].…”
Section: Discussionmentioning
confidence: 99%
“…CXCR6 is also involved in the formation of the immunological synapse upon interaction with its ligand CXCL16, a membrane-bound chemokine expressed by DC [62,93]. This interaction my lead to efficient transmission of HIV within the virological synapse [94]. CXCL16 is also expressed by CD16 + monocytes [95].…”
Section: Discussionmentioning
confidence: 99%
“…DCs are involved in maintaining a balance between tolerance versus protective immunity at both the innate and adaptive levels, which process is pivotal at mucosal sites, where immune homeostasis processes warrant peripheral integrity, and where the main battle with HIV takes place [14]. Recent studies have demonstrated the importance of cross-talk between epithelial cells and mDC populations in maintenance of a homeostatic balance of regulatory versus inflammatory responses at the mucosal level [7375].…”
Section: The Importance Of Dcs At Mucosal Sitesmentioning
confidence: 99%
“…There, DCs are one of the earliest cell types to be exposed to the virus and present an inherent capacity to orchestrate a homeostatic balance between tolerance and protection [14]. It is likely that the incapacity to keep a balance in these homeostatic processes will promote inflammation and lead to disease progression [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, application of this technique would open possibilities for a more detailed investigation of HIV-1 cell‑to-cell transmission in 3d tissue cultures. In in vivo systems, directed virus release and transmission through direct contacts between infected cell and uninfected cells (so-called virological synapses) represents an effective pathway of HIV-1 transmission (for reviews see [101,102,103,104]). However, quantitative kinetic analyses of HIV-1 budding site formation have so far been limited to TIRF microscopy, which cannot visualize intracellular synapses, and were restricted to flat adherent model cell lines instead of the physiological target cells.…”
Section: Future Directionsmentioning
confidence: 99%